Impact of COVID-19 Infection on the Outcome of Patients With Ischemic Stroke. Issue 12 (December 2021) - Martí-Fàbregas, Joan; Guisado-Alonso, Daniel; Delgado-Mederos, Raquel; Martínez-Domeño, Alejandro; Prats-Sánchez, Luis; Guasch-Jiménez, Marina; Cardona, Pere; Núñez-Guillén, Ana; Requena, Manuel; Rubiera, Marta; Olivé, Marta; Bustamante, Alejandro; et al.
Abstract : Background and Purpose: We evaluated whether stroke severity, functional outcome, and mortality are different in patients with ischemic stroke with or without coronavirus disease 2019 (COVID-19) infection. Methods: A prospective, observational, multicentre cohort study in Catalonia, Spain. Recruitment was consecutive from mid-March to mid-May 2020. Patients had an acute ischemic stroke within 48 hours and a previous modified Rankin Scale (mRS) score of 0 to 3. We collected demographic data, vascular risk factors, prior mRS score, National Institutes of Health Stroke Scale score, rate of reperfusion therapies, logistics, and metrics. Primary end point was functional outcome at 3 months. Favourable outcome was defined depending on the previous mRS score. Secondary outcome was mortality at 3 months. We performed mRS shift and multivariable analyses. Results: We evaluated 701 patients (mean age 72.3±13.3 years, 60.5% men) and 91 (13%) had COVID-19 infection. Median baseline National Institutes of Health Stroke Scale score was higher in patients with COVID-19 compared with patients without COVID-19 (8 [3–18] versus 6 [2–14], P =0.049). Proportion of patients with a favourable functional outcome was 33.7% in the COVID-19 and 47% in the non-COVID-19 group. However, after a multivariable logistic regression analysis, COVID-19 infection did not increase the probability of unfavourable functional outcome. Mortality rate was 39.3% among patients with COVID-19 and 16.1% in the non-COVID-19 group. In the multivariable logistic regression analysis, COVID-19 infection was a risk factor for mortality (hazard ratio, 3.14 [95% CI, 2.10–4.71]; P <0.001). Conclusions: Patients with ischemic stroke and COVID-19 infection have more severe strokes and a higher mortality than patients with stroke without COVID-19 infection. However, functional outcome is comparable in both groups. Abstract : Supplemental Digital Content is available in the text.